2003
DOI: 10.1037/0278-7393.29.5.894
|View full text |Cite
|
Sign up to set email alerts
|

Exterior letters are not privileged in the early stage of visual word recognition during reading: Comment on Jordan, Thomas, Patching and Scott-Brown (2003).

Abstract: Potential sources for the discrepancy between the letter position effects in T. R. Jordan, S. M. Thomas, G. R. Patching, and K. C. Scott-Brown's (2003; see record 2003-07955-013) and D. Briihl and A. W. Inhoff s (1995; see record 1995-20036-001) studies are examined. The authors conclude that the lack of control over where useful information is acquired during reading in Jordan et al.'s study, rather than differences in the orthographic consistency and the availability of word shape information, account for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Thus, this hypothesis relies on the importance of the beginning letters in word identification. There is, however, currently some debate in the literature over whether it is beginning letters (see Briihl & Inhoff, 1995; Inhoff, Radach, Eiter, & Skelly, 2003) or exterior letter pairs (Jordan, Thomas, Patching, & Scott-Brown, 2003; Jordan, Thomas, & Patching, 2003; see also White et al, in press) that are most important for word recognition. Previous studies have suggested that insertion of spaces increases perceptibility of letters for foveally presented letter strings in certain tasks (Campbell & Mewhort, 1980; Estes & Wolford, 1971; Mewhort, Marchetti, & Campbell, 1982; Shaw, 1969; Wolford & Holingshead, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this hypothesis relies on the importance of the beginning letters in word identification. There is, however, currently some debate in the literature over whether it is beginning letters (see Briihl & Inhoff, 1995; Inhoff, Radach, Eiter, & Skelly, 2003) or exterior letter pairs (Jordan, Thomas, Patching, & Scott-Brown, 2003; Jordan, Thomas, & Patching, 2003; see also White et al, in press) that are most important for word recognition. Previous studies have suggested that insertion of spaces increases perceptibility of letters for foveally presented letter strings in certain tasks (Campbell & Mewhort, 1980; Estes & Wolford, 1971; Mewhort, Marchetti, & Campbell, 1982; Shaw, 1969; Wolford & Holingshead, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…For example, fixations land further into words with regular as compared with irregular beginnings (Hyönä, 1995; Radach, Inhoff, & Heller, 2004). Different spatial formats of the identical compound word lead to different saccade targeting strategies, each of which is designed to land near the centers of spatially distinct letter groupings (Inhoff, Radach, Eiter, & Skelly, 2003).…”
mentioning
confidence: 99%
“…Based on these and similar findings Schotter et al (2012, p. 14) concluded in their recent review on parafoveal processing that “having the first two or three letters preserved in the preview facilitates processing of the target word” (see also Rayner, Well, Pollatsek, & Bertera, 1982). The Briihl and Inhoff study triggered an interesting debate with Jordan and colleagues, who found evidence for a particular role of the exterior letters (i.e., the initial and the final letters) for word recognition (Inhoff, Radach, Eiter, & Skelly, 2003; Jordan, Thomas, & Patching, 2003; Jordan, Thomas, Patching, & Scott-Brown, 2003). An issue of the dispute was the application of parafoveal masks—essentially that one should not apply parafoveal masks without explicitly ensuring that the masks do not lead to uncalled-for side effects (Jordan, Thomas, et al, 2003).…”
mentioning
confidence: 99%